Lack of H+-pyrophosphatase Prompts Developmental Damage in Arabidopsis Leaves on Ammonia-Free Culture Medium - Fukuda, Mayu; Segami, Shoji; Tomoyama, Takaaki; Asaoka, Mariko; Nakanishi, Yoichi; Gunji, Shizuka; Ferjani, Ali; Maeshima, Masayoshi (Frontiers in Plant Science, 2016)
The plant vacuolar H+-pyrophosphatase (H+-PPase) functions as a proton pump coupled with the hydrolysis of pyrophosphate (PPi). Loss-of-function mutants (fugu5s and vhp1) of the H+-PPase of Arabidopsis thaliana show clear morphological phenotypes in the cotyledons, caused by inhibition of gluconeogenesis from seed storage lipids due to excessive accumulation of PPi. In this study, we investigated the phenotypes of the fugu5 and vhp1 mutants during vegetative growth under a specific nitrogen nutritional regime. When nitrate in the culture medium was the sole nitrogen source, growth of the mutant rosette leaves was severely compromised. Interestingly, trypan blue staining revealed notable cell death at the leaf blade–petiole junctions of young leaves, a region known to have meristematic features. Physical contact of the leaf tip with the culture medium also triggered leaf atrophy, suggesting that absorption of some elements through the hydathodes was probably involved in this phenotype. Prevention of such leaf–medium contact resulted in a marked decrease in phosphate content in the shoots, and suppressed leaf atrophy. Furthermore, fugu5 necrotic symptoms were rescued completely by heterologous expression of yeast cytosolic soluble pyrophosphatase IPP1 or uncoupling-type mutant H+-PPases that retained only PPi-hydrolysis activity, indicating that the damage of actively proliferating cells was caused by the loss of the PPi-hydrolyzing function of H+-PPase. Importantly, cell death and growth defects of the fugu5 leaves were suppressed completely by the simple addition of ammonium (>1 mM) to the culture medium. The PPi content in the shoots of fugu5 grown on ammonium-free medium was 70% higher than that of the wild type, and PPi levels were restored to normal upon growth on ammonium-supplemented medium. Together, these findings suggest that the PPi-hydrolyzing activity of H+-PPase is essential to maintain the PPi contents at optimal levels when grown on ammonium-free culture medium, and any direct contact of the leaves with the culture medium may raise PPi levels in the leaves through increased phosphate uptake.